(untitled) (Global Journal of Management and Business Research, 2024)
This research delves into the intricate economic repercussions of Brexit on migrant entrepreneurs and host rural communities in Scotland. Data collection employed a combination of 275 questionnaires distributed across 10 rural areas and in-depth insights drawn from a total of six focus group discussions. Specifically, three focus groups were conducted with migrant entrepreneurs operating businesses in rural areas, offering a profound exploration of their unique challenges, experiences, and perspectives. Additionally, three separate focus groups were conducted with the host communities, encompassing rural residents and third-party stakeholders, including local government representatives and community organizations. The questionnaire yielded responses from a diverse sample, with 115 valid responses after rigorous data cleaning. The research utilizes a mixed-methods approach, intertwining quantitative and qualitative analyses. The quantitative analysis employs a non-parametric Kruskal-Wallis H test to examine the disparities in perceptions of Brexit’s economic impact between migrant entrepreneurs and host rural communities across the 10 surveyed rural areas.